Transistor Efek Medan Berbasis Semikonduktor Organik Pentacene untuk Sensor Kelembaban - Fadliondi; Budiyanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
The purpose of this paper is to fabricate a humidity sensor from organic semiconductor and to understand the effect of the transistor`s structure on the sensitivity of humidity sensor. Organic MOSFETs were fabricated using organic semiconductor called pentacene. The structures were bottom-contact and top-contact. The bottom-contact pentacene MOSFET was more sensitive to humidity than the top-contact pentacene MOSFET was. When the relative humidity increased from 20 % to 70 %, for VGS = VDS = -5 V, the magnitude of drain source current of the MOSFET decreased from 0.45 µA to 0.1 µA for bottom-contact pentacene MOSFET and from 3.6 µA to 3 µA for top-contact pentacene MOSFET. As the relative humidity increased from 20 % to 70 %, for VGS = 2 V and VDS = -5 V, the magnitude of drain source current of the MOSFET increased from 0.77 nA to 3 nA for bottom-contact pentacene MOSFET and from 0.6 nA to 1.4 nA for top-contact pentacene MOSFET. As the relative humidity increased from 20 % to 70 %, the threshold voltage shifted toward positive direction, from 0.5 V to 2 V for bottom-contact pentacene MOSFET and from 1 V to 2 V for top-contact pentacene MOSFET. The result showed that the pentacene MOSFET with bottom-contact structure was more suitable for humidity sensor than that with top-contact structure.